2019
DOI: 10.1186/s12909-018-1434-5
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles of physiotherapists: a systematic scoping review

Abstract: BackgroundUnderstanding students’ learning styles, and modifying teaching styles and material accordingly, is an essential to delivering quality education. Knowing more about the learning styles of physiotherapy learners will assist educators’ planning and delivering of learning activities. The purpose of this scoping review was to explore what is published about physiotherapy learning styles.MethodsAn adapted Arksey and O’Malley framework was applied to undertake this systematic scoping review. Nine electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 38 publications
4
56
0
2
Order By: Relevance
“…Despite calls for education and training of clinicians who work with patients with dementia [20], reviews have identified that dementia education is limited for medical, nursing and allied healthcare professionals [10]. Our findings indicate that physiotherapists value more informal educational opportunities, learning through active participation with experienced peers in the work-place, a finding supported by literature on the preferred learning styles of physiotherapists [11]. However in order for training and education to be most effective, it is important that active participation with practice-based learning is underpinned by theoretical or knowledge-based content [18].…”
Section: Comparison With Previous Researchsupporting
confidence: 59%
See 1 more Smart Citation
“…Despite calls for education and training of clinicians who work with patients with dementia [20], reviews have identified that dementia education is limited for medical, nursing and allied healthcare professionals [10]. Our findings indicate that physiotherapists value more informal educational opportunities, learning through active participation with experienced peers in the work-place, a finding supported by literature on the preferred learning styles of physiotherapists [11]. However in order for training and education to be most effective, it is important that active participation with practice-based learning is underpinned by theoretical or knowledge-based content [18].…”
Section: Comparison With Previous Researchsupporting
confidence: 59%
“…Definitive information about undergraduate dementia content in programmes across health and social care has been difficult to ascertain [10]. The design of educational programmes for physiotherapists needs to take their clinical experiences, learning styles and educational needs into consideration [11]. However, there is a paucity of literature on the dementia care educational needs of physiotherapists.…”
Section: Introductionmentioning
confidence: 99%
“…Professional culture may influence how individuals learn by how they process and utilize information and how effectively a CPG may be implemented in a specific context P2: “… culture eats strategy for breakfast ‐ so the culture of the team is going to determine to a large extent how the team practices and behaves and communicates and collaborates … no one can have all the answers and so using a guideline as a starting point is great …”…”
Section: Resultsmentioning
confidence: 99%
“…It is also beneficial to explore the preferred learning/working styles (Nja et al, 2019;Stander, Grimmer and Brink, 2019) and working practices within the group. Who enjoys new experiences?…”
Section: Co-create a Mission Statement And Identify Individual Objectmentioning
confidence: 99%